IMPLEMENTASI PROSEDUR ADMINISTRASI KONTRAK STANDAR (STUDI KASUS PADA PROYEK PRESISI 5 POLRI) - Edison Hatoguan Manurung; Kerlima Hutagaol; Dizzy Putrafakhmi (SINERGI : Jurnal Riset Ilmiah, 2026)
Contract administration is a crucial aspect of successful construction project implementation, particularly for government projects with high levels of complexity, accountability, and risk. This study aims to analyze the implementation of standard contract administration procedures in the Presisi 5 POLRI Project, identify its level of compliance with applicable regulations, and examine obstacles and improvement efforts. The research method used was a descriptive qualitative method with a case study approach. Data collection techniques included reviewing contract documents, field observations, and interviews with relevant parties. The results indicate that, in general, contract administration procedures have been implemented according to standards, but several obstacles remain in aspects such as documenting work changes, time management, and coordination between parties. This research is expected to provide practical contributions as evaluation material and recommendations for improving the quality of contract administration in government construction projects..